The Main Trends and Prospects of Development of International Tourism - Krasnokutskiy, Pavel A.; Kulchittskij, Alexey V.; Perova, Tatyana V.; Bystrova, Natalia V.; Khizhnaya, Anna V. (International Journal of Economics and Financial Issues, 2016)
In the global economy of today, there is a tendency for progressive development, there has been expansion in the volume of trade in the international market, modernization of the transport sector, increasing the internalization and globalization of world economic spheres, increasing the number of contractual alliances, visits of the population related to economic activity. Currently, there is actively progressing the development of the world services to the public as the formation and organization of international tourism. This area in the modern context is one of the most important global economic activity, is a difficult and complex procedure which has no small influence on the structuring and the overall picture of the development of the world economy and the state. Disclosure of the major issues of the development of international tourism in global society reveals one of the urgent problems of the world - understanding tourism and its development trends. The main objective is to study the main provisions of international tourism market of the world powers. The main tasks of the disclosed topics: analysis of statistics of international tourism; the impact of major internal and external factors impact on tourism; identification of prospects of development and formation of international tourism. Keywords: tourism, world community, competition, market, development trend, economy JEL Classifications: L83, Z30, Z32, F63